Identification and validation of a prognostic signature of autophagy, apoptosis and pyroptosis-related genes for head and neck squamous cell carcinoma: to imply therapeutic choices of HPV negative patients - Nan, Zhaodi; Dou, Yu; Chen, Anwei; Wang, Ketao; Sun, Jintang; Meng, Zhen; Neckenig, Markus; Ai, Dan; Liu, Shaohua; Dong, Zuoqing; Ma, Chao; Cheng, Yufeng; et al. (Frontiers in Immunology, 2023)
Introduction An effective tool is needed to predict the prognosis of head and neck squamous cell carcinoma (HNSCC). Human papillomavirus (HPV) positive HNSCC patients generally have a favorable survival and a promising responsiveness to radiotherapy, chemoradiotherapy and checkpoint blockades. However, HPV negative patients, the majority of HNSCC patients, have been largely overlooked. Cell death has been involved in the therapeutic resistance of cancers. To this end, we aimed to identify the association of autophagy, apoptosis and pyroptosis-related genes with the prognosis of HNSCC, and construct a prognostic signature to predict the prognosis for HNSCC, especially for HPV negative HNSCC. Methods Autophagy and apoptosis-related genes were obtained from Gene Set Enrichment Analysis (GSEA) website, and pyroptosis-related genes were obtained from GSEA and Gene Ontology (GO) database. We established the cell death index (CDI) based on RNA sequencing (RNA-seq) data and clinicopathological information from The Cancer Genome Atlas (TCGA) dataset. The prognostic value of CDI was verified by Kaplan-Meier, receiver operating characteristic (ROC) and univariate and multivariate Cox regression analyses in TCGA dataset, and validated with the datasets from Gene Expression Omnibus (GEO) and Qilu Hospital of Shandong University. We further assessed the immune microenvironment of patients with high and low CDI scores. Moreover, the expression of the signature genes in HNSCC cell lines were explored. Results We found that CDI was an independent prognostic indicator for overall survival (hazard ratio 3.80, 95% confidential interval: 2.70-5.40, P < 0.001). Furthermore, HNSCC patients with high CDI scores obtained increased overall survival post radiation indicating benefits from radiotherapy of this subgroup. On the other hand, HPV negative HNSCC patients with low CDI exhibited increased checkpoint gene expressions, an inflamed tumor microenvironment and an enriched immune response-related functions, suggesting the potential benefits from checkpoint immunotherapies of this subgroup. Moreover, we validated the baseline and induced expressions of above 16 genes in two HPV negative HNSCC cell lines, CAL27 and SCC-15. Discussion We established a prognostic signature and emphasized its implements in the therapeutic choices of HPV negative HNSCC patients, the majority and the poor outcome population of HNSCC.